Peningkatan Hasil Belajar Materi Shalat Gerhana Menggunakan Pembelajaran Kooperatif Tipe Team Game Turnamen Pada Siswa Sekolah Menengah Pertama - Rafki Parifia; Muhammad Ari Khairan; Almer Ragil Amri; Abdul Ghanif Herlambang; Wismanto Wismanto (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Education is the forerunner of the birth of an intelligent generation. Education does not only take place at one moment, but education continues without knowing the age called lifelong education. In the teaching and learning process it is necessary to create comfortable conditions for students to learn. Therefore, today many learning models are applied in the learning process. This classroom action research aims to apply the Team Games Tournament (TGT) learning model in the teaching and learning process by optimizing the active role of students in the classroom and providing evaluations to measure student understanding of the material through the Team Games Tournament (TGT) learning model. The subjects of this study were junior high school students. The estimated duration of the study lasted at least one month. The timing of research refers to the school's academic calendar, because PTK requires several cycles that require an effective teaching and learning process in the classroom. In the learning process, there are several improvements that occur in students where based on the results of observing student attitudes in class during learning activities through the Teams Games Tournament (TGT) method it turns out to be able to change student learning attitudes and can improve student mindsets and learning activities and foster a sense of mutual cooperation between students.